Membuka Pintu Hiburan di Era Kolonial: Sejarah Perkembangan Bioskop di Batavia, 1900-1942 - Agustin, Nurmalia; Ismawati, Deby Ayu; Fauziah, Mustasyifa (Mahesa Research Center (PT. Mahesa Global Publishing), 2023)
This research aims to discuss the history of cinema in Batavia from entertainment before the existence of cinemas, the background of the beginning of cinemas to Chinese involvement in the cinema industry. Of course, in the past, watching in theaters already existed during the Dutch colonial period. Movie theaters have existed in Batavia since 1900. The culture of watching this movie began to enter in the early 20th century where the indigenous people at that time called the moving image